The formation of young athletes' specialization on the example of rhythmic gymnastics group exercises - I.S. Syvash (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose : to substantiate the approach to the formation of specializations gymnasts in the initial stages and preliminary basic training. On this basis, to develop the technology selection, orientation and training of athletes in rhythmic gymnastics group exercises. Material : an expert survey of 46 coaches and judges of Ukraine calisthenics different skills training for gymnasts to group exercise. The study involved 50 athletes who are at the initial stages and preliminary basic training. Results : the necessity of forming specialization. Presented educational technology selection, orientation and training gymnasts in group calisthenics exercises. Investigated the components and benefits of the proposed technology. Systematized criteria for selecting gymnasts to group exercise. Conclusions: experimentally proven technology selection, orientation and training of athletes in the group exercise. The main results of the study have been practically implemented in the training process of training young athletes.